Role of Ethanol Lock Therapy Vs Heparin Lock In Preventing Infections in Non-Tunneled Hemodialysis Catheters - Shrestha, Sagar KD; Raut, K. B. (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: This study aims to determine the rate of catheter related bloodstream infection using intraluminal 70% ethanol lock 20 min prior to initiation of hemodialysis in comparison with heparin lock and also to study adverse events with the use of locks. MATERIAL AND METHODS: Out of 196 patients, eligible 128 patients who under went hemodialysis in Tribhuwan University Teaching Hospital, were randomly allocated to 68 jugular catheterization with ethanol lock or heparin lock and 60 femoral catheterization with ethanol lock or heparin lock. 5 patients with jugular catheter with ethanol lock and 3 patients with heparin lock changed center. The major outcomes were catheter-related blood stream infection (CRBSI) or thrombosis or other adverse effects. RESULTS: According to KDIGO definition of CRBSI, definite CRBSI occurred in 22 (18.33%) patients in Heparin group, probable CRBSI occurred in 31 (25.83%) patients in Heparin whereas definite CRBSI occurred in 1 (1.38%) patient in Ethanol group, and possible CRBSI occurred in 18 (15.00%) patients in Ethanol group. Most common organisms isolated were Staphylococcus aureus and Enterococcus faecalis in heparin group. No adverse events occurred in ethanol group. CONCLUSION: Our study has suggested Ethanol lock therapy is effective in preventing CRBSI as there were fewer CRBSI in ethanol lock in comparision to heparin lock which needs to studied in large population.